2010
DOI: 10.1007/s10578-010-0179-0
|View full text |Cite
|
Sign up to set email alerts
|

Familism, Parent-Adolescent Conflict, Self-Esteem, Internalizing Behaviors and Suicide Attempts Among Adolescent Latinas

Abstract: Adolescent Latinas continue to report higher levels of suicide attempts than their African-American and White peers. The phenomenon is still not understood and is theorized to be the result of the confluence of many cultural, familial, and individual level factors. In Latino cultures, belief in the importance of the family, the value known as familism, appears to protect youth's emotional and behavioral health, but parent-adolescent conflict has been found to be a risk factor for suicide attempts. The role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
140
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 59 publications
14
140
2
3
Order By: Relevance
“…Adolescent familism also predicted low levels of parent-adolescent conflict (e.g., Smokowski, Rose, & Bacallao, 2010), and conflict served to mediate the positive effects of attitudinal familism. However, consistent with tenets of developmental science regarding the individual's transaction with the surrounding context, research has found that family conflict in the presence of high levels of attitudinal familism may be more detrimental as it violates the expectations of family harmony ( Hernández, Ramírez Garcia, & Flynn, 2010;Kuhlberg, Peña, & Zayas, 2010).…”
Section: Family Functioningmentioning
confidence: 87%
See 1 more Smart Citation
“…Adolescent familism also predicted low levels of parent-adolescent conflict (e.g., Smokowski, Rose, & Bacallao, 2010), and conflict served to mediate the positive effects of attitudinal familism. However, consistent with tenets of developmental science regarding the individual's transaction with the surrounding context, research has found that family conflict in the presence of high levels of attitudinal familism may be more detrimental as it violates the expectations of family harmony ( Hernández, Ramírez Garcia, & Flynn, 2010;Kuhlberg, Peña, & Zayas, 2010).…”
Section: Family Functioningmentioning
confidence: 87%
“…Finally, other studies have considered discrepancies in parent and child reports of attitudinal familism. Parentchild alignment on attitudinal familism was protective against both internalizing and externalizing symptoms ( Bamaca-Colbert & Gayles, 2010;Baumann, Kuhlberg, & Zayas, 2010;Kuhlberg, Peña, & Zayas, 2010;Stein & Polo, 2014).…”
Section: Psychosocial and Academic Outcomesmentioning
confidence: 99%
“…Niveles bajos en los jóvenes se han asociado con síntomas psicopatológicos como reacciones de ansiedad 12 , depresión, desesperanza y tendencias suicidas 13 , demoras innecesarias en la realización de tareas y son comúnmente observados en aquellos que presentan conductas agresivas 14 , conductas antisociales 15 o violencia escolar 16 .También es fundamental analizar que los niños y jóvenes con baja autoestima se caracterizan por presentar una peor salud física, encontrando que los sujetos que llegan a la adolescencia con baja autoestima tienen un riesgo mayor de presentar hábitos no saludables y una salud mental más pobre 17 .…”
Section: E L Ministerio De Salud De Chile a Través Deunclassified
“…Risk factors for suicidal behaviour during adolescence mainly include depressed mood, mental disorders, substance abuse, intrapsychic problems (i.e., a negative self-image, issues related to emotional control, anxiety, impulsivity, the presence of borderline personality traits, the presence of antisocial characteristics, the presence of the characteristics of narcissism), social isolation, loneliness, traumatic experiences involving, e.g., violence, sexual abuse, loss of significant others, as well as conflicted and dysfunctional family relationships, illness in the family, low economic status of the family, the family and social transmission regarding destruction (Adrian, Miller, McCauley, & Vander Stoep, 2016;Brausch & Gutierrez, 2010;King, Kerr, Passarelli, Foster, & Merchant, 2010;Kuhlberg, Peña, & Zayas, 2010;Miller, Rathus, & Linehan, 2007;Pilecka, 2005;Steele & Doey, 2007;Woźniak, Talarowska, Orzechowska, Florkowski, & Gałecki, 2013). The indicated factors increase the risk of violent behaviour in adolescents (Arim, Dahinten, Marshall, & Shapka, 2011;Crapanzo, Frick, & Terranova, 2010;Herba, Tranah, Rubia, & Yule, 2006;Manseau, Fernet, Hébert, Collin-Vézina, & Blais, 2008;Pajer, Leininger, & Gardner, 2010;Rulison, Gest, Loken, & Welsh, 2010;Undheim & Sound, 2010).…”
Section: Self-image and Suicidal And Violent Behaviours Of Adolescentmentioning
confidence: 99%